The Effect of Using Picture Word Inductive Model (PWIM) on Students Writing Descriptive Paragraphs Ability - Nurwandya, Irnanda Putri; Hanafi, Hanafi; Astutik , Indri (Universitas Muhammadiyah Jember, 2023)
Mastering writing is a fundamental skill that can be challenging even for native speakers. In this research, a quantitative experimental design was employed. Specifically, a quasi-experimental design with a non-equivalent control group design was utilized. The research subject is first grade students of SMPN 01 Sumberbaru Jember which covers up to 56 students which devided into two groups (experimental group and control group). The data are collected by using writing test and paying attention to content, organization, vocabulary, language use and writing mechanics. The findings of the research indicated a significant difference in scores between students who were taught using the Picture Word Inductive Model and those who were not. According to the statistical calculations, the experimental group attained a mean posttest score of 79.57, while the control group obtained a mean score of 60.14. The two-tailed significance value (sig) was found to be 0.00, which is below the alpha level of 0.05. Consequently, the null hypothesis (Ho) was rejected, and the alternative hypothesis (H1) was accepted. In conclusion, the Picture Word Inductive Model (PWIM) proved to be an effective approach for teaching writing descriptive paragraphs to junior high school students.